(untitled) (Pulse, 2010)
Myasthenia gravis (MG) is an autoimmune disorder of the neuromuscular junction. The disease is characterized by exacerbation and remission of the symptoms from time to time. Myasthenic crisis is a serious complication of MG and is defined as weakness from acquired MG that is severe enough to require intubations [1]. Myasthenic crisis may complicate in 15-20% of patient with MG [2], [3]. Most patients require ventilation for a brief period, usually less than two weeks [4]. Repeated intubations may cause tracheal stenosis. The potential risk factors for post-intubation subglottic stenosis include, the underlying disease requiring endotracheal intubations(EI), the age and body weight, the duration and number of EIs, absence of sedation and the occurance of infections, hypotensive or hypoxic events during the period of EI and traumatic EI [5], [6]. Key words: Tracheal stenosis, Repeated intubations, Myasthenia gravis. DOI: 10.3329/pulse.v3i1.6550 Pulse Vol.3(1) July 2009 p25-26